Six-membered ring systems: with O and/or S atoms - Santos, Clementina M.M. (2013)
The year 2011 was particularly rich in reviews involving the synthesis and transformations of a wide structural range of 0- and S-6-membered heterocycles and some on their biological properties, reflecting their importance for the scientific conmmnity. An overview on the structure and biological activity of naturally occurring withanolides < 11 NPR 705> and a review on structure, biological activity, and synthesis ofplant polyphenols < 11AGE586>, matine natural products < 11 NPR196, 11NPR269>, and aromatic cyclopenta[c]pyrans < 11JHC747> have appeared. The synthesis of the vatious structural subcategoties oflimonoids has also been surveyed <11EJ019>. More specific reviews include a critical attempt to discuss a structure-activity relationship among a series of trioxane- and tetraoxane-based compounds < 11CMC3889>, and a report on the bioactivity and scope of the synthetic methods of chromenopyridines, with emphasis on multicomponent and robust methodologies, as well as reactivity issues and medical applications < 11 CMC4761 > . The powerful synthetic strategy using the thiopyran template route to the enantio- and diastereoselective synthesis of polypropionates, and some natural products or synthetic key intermediates, has been reviewed <11CC1 1375>.